Antibacterial and anti-HIV metabolites from marine streptomyces albus MAB56 isolated from Andaman and Nicobar Islands, India - Manikkam, Radhakrishnan; Murthy, Sangeetha; Palaniappan, Sivasankar; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Ganesan, Vijayalakshmi; Kannan, Sivakumar; Ramasamy, Balagurunathan; Thirugnanasambandan, Somasundaram; Dastager, Syed G.; Hanna, Luke Elizabeth; et al. (Applied Biochemistry and Biotechnology, 2023)
Marine-derived actinobacteria have tremendous potential to produce novel metabolites with diverse biological activities. The Andaman coast of India has a lot of microbial diversity, but it is still a relatively unknown ecology for isolating novel actinobacteria with beneficial bioactive compounds. We have isolated 568 actinobacterial strains from mangrove rhizosphere sediments and sponge samples. Crude extracts from 75 distinct strains were produced by agar surface fermentation and extracted using ethyl acetate. In the disc diffusion method, 25 actinobacterial strains showed antimicrobial activity; notably, the strain MAB56 demonstrated promising broad-spectrum activity. Strain MAB56 was identified as Streptomyces albus by cultural, microscopic, and molecular methods. Conditions for bioactive metabolites from MAB56 were optimized and produced in a lab-scale fermenter. Three active metabolites (C1, C2, and C3) that showed promising broad-spectrum antimicrobial activity were isolated through HPLC-based purification. Based on the UV, FT-IR, NMR, and LC-MS analysis, the chemical nature of the active compounds was confirmed as 12-methyltetradecanoic acid (C1), palmitic acid (C2), and tridecanoic acid (C3) with molecular formulae C14H28O2, C16H32O2, and C13H26O2, respectively. Interestingly, palmitic acid (C2) also exhibited anti-HIV activity with an IC50 value of < 1 mu g/ml. Our findings reveal that the actinobacteria from the Andaman marine ecosystems are promising for isolating anti-infective metabolites.
Keywords: actinobacteria; Andaman Islands; anti-HIV; Antibacterial; Bioactive metabolites